Development and comparative analysis of yeast protein extraction protocols for mass spectrometry - Almeida, Lauana Fogaça de [UNESP]; Moraes, Leonardo Nazário de [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Valente, Guilherme Targino [UNESP] (Elsevier, 2019)
Mass spectrometry is the most used method for protein identification and quantification. Here we developed four protein extraction protocols precisely for mass spectrometry, and we compared with other ones already published. The best protocol developed by us consists on a simple extraction solution, a heat-shock step, and does not use protease inhibitor; moreover, it is the most efficient and uniform among replicates, besides to be safe, cheap and fast. That method also provided the highest number of proteins uniquely identified and allows finding a diversity of protein classes, which their absence is a problem to be avoided.
Keywords: Protein extraction protocol; Proteomics; Protocol comparisons; Saccharomyces cerevisiae proteins